Nós queremos reitores negros, saca?: trajetórias de universitários negros da classe média na UFMG - Ricardo Dias de Castro (2017)
CASTRO, R. D. (2017) - We want black rectors, you know?: trajectories of black university students of the middle class of UFMG. Masters Dissertation, Faculdade de Filosofia e Ciências Humanas, Departamento de Psicologia, Universidade Federal de Minas Gerais, Belo Horizonte. The contemporary racial atmosphere in Brazil cannot be compared to the racial scene thirty years ago. And although racism is a structuring element of Brazilian social dynamics, the dilemmas around racial relations are no longer only in the subalternization, violence and oppression of the black people. In fact, debates and mobilization for the reversal of racial inequalities have been broadened, for example, Affirmative Actions and other policies of inclusion and valorization of the black population in the country. In this direction, studies on black middle-class have become a broad and complex field of investigation to construct tools and practices which help to uncover Brazilian racism and to consolidate strategies to combat it. In this research, we carried out the construction of a field theme that aimed to understand the trajectories of black middle-class university students from UFMG. The articulation between Epistemological-theoretical-methodological elaborations and the use of the narratives of eight black middle-class university students allowed us to recognize a new social imaginary about rising blacks. This breaks with the historical incompatibility between being black and having power to enjoy the goods associated with modernity. These subjects point to the fact that they are, for the most part, the second generation of black middle-class in their families, which has therefore enabled them to have access to a basic education that guarantees entrance into public higher education and to a series of privileges that have allowed them the accumulation to economic and cultural goods. They also denounce how the university has been a space, daily, re-signified by the presence of blacks and antiracist debate from the action of political and cultural movements that reverberate within the walls in public higher education. What is perceived, fundamentally, is that, even with the existence of practices of prejudice and discrimination in the spaces where they are, these young people have been trying to re-signify the values of the Brazilian middle-class, making it broader and more democratic from black references. The university and the middle-class have become for these university students a strategic place of power for action and intervention in order to question whiteness, consumption and elitism as the sole norm of the organization of society.